ANALISIS KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KOTA SAMARINDA - 125, ISNAWATI ISNAWATI (EKONOMIA, 2017)
This study aims to determine and measure the level of tax contribution of the Hotel Tax on Samarinda Original Income in 2009-2015.The method used in this research is descriptive quantitative. The data used in this study secondary data, which includes target data and hotel tax realization. Data collection techniques were conducted with field research and research to library. TheÂ  contribution ratio analysis to know the to wich local taxes contribute to PAD revenue.Based on the research results can be concluded that based on contribution ratio analysis shows that the hotel tax in 2009 the contribution of hotel taxes on the percentage of 4.34% criteria â€œvery lessâ€. In 2010 it increased by 5.67% â€œvery lessâ€ criteria. 2011 and 2012 decreased respectively in 2011 by 4.69% and by 2012 by 4.19% â€œvery lessâ€. 2013 and 2014 have decreased with the criteria of â€œvery lessâ€. While the year 2015 increased percentage by 5.05% â€œvery lessâ€ criteria. Tax Hotel contributions tend to be where the difference with an averange of 4.44% then the hypothesis is â€œAcceptedâ€.Â